PENGGUNAAN ABU CANGKANG SAWIT SEBAGAI PENGGANTI PADA SEBAGIAN SEMEN UNTUK MENAMBAH KEKUATAN TEKAN MORTAR - Khairil Anwar; Mawardi Mawardi (Inersia: Jurnal Teknik Sipil, 2019)
The objective of this research was to investigate the influence of palm ash powder as a substitute for a fraction of the cement to the mortar compressive strength. Palm ash constitutes as cesspool of palm production that contains a lot of silica element (SiO) and constitutes pozzolanic material. The sample used were cubes size 50 mm x 50 mm x 50 mm. Sand that used have 2 variation are mountain sand and sea sand and have 2 processing are washing and not washing. The method that used is anava 2 way. The testing object was made by composition of mixture 1 cement : 2 sand and 1 cement : 4 sand, by variation of palm ash addition on cement 0%, 7.5%, 12.5%, 25%, and 30%. By the research showed pressure strength respectively viz 38.52 MPa, 21.85 MPa, 17.10 MPa, 7.66 MPa, and 5.59 MPa. The test was conducted after the mortar was 28 days old. The test result of mortar found that higher content of the fruit bunch ash so lower of compressive mortar strength. So that the objective of this research dont have optimum percentage of palm ash to compressive strength of mortar and palm ash dont used as a subsitute for a fraction of cement to the mortar compressive strength.